Methodology for improving speed and strength endurance of qualified taekwondo athletes at the stage of improving their sports skills - Misbakhov, A.A.; Zalyalieva, O.V.; Sungatullin, R.I. (Theory and Practice of Physical Culture, 2025)
Purpose of the study. To theoretically substantiate the methodology for improving speed and strength endurance in qualified taekwondo athletes at the stage of improving their sports skills. Methodology and organization of research. To substantiate the methodology, a pedagogical experiment was conducted on the basis of PovGUFKSiT with qualified taekwondo athletes. An experimental group (n=10) and a control group (n=10) were created for the experimental work. We used the following research methods: analysis of scientific and methodological literature; pedagogical testing; pedagogical experiment; mathematical and statistical methods. Research results and conclusions. A method of developing the speed and strength endurance of qualified taekwondo practitioners was developed, which was included in the content of the main part of the training session. The methodology includes the following principles: gradualness; individual approach; compliance with the means and methods of training; compliance with the FSSP for the sport "taekwondo". Classes according to the experimental method were held for 20 weeks, 2 times a week. In total, 40 classes were held, where the methodology was given 30 minutes. The main means were: special-preparatory exercises, exercises on special equipment, working in pairs on equipment with a partner in full ammunition, competitive fights.